A study on the nonlinear elastic behavior of ballistic gelatin using a rotational rheometer. (October 2019) - Liu, L; Ding, C; Lu, Q Q; Zhang, X F
Abstract: The present work was focused on the study of large elastic behavior and constitutive modeling of ballistic gelatin. The simple shear tests were conducted using a rotational rheometer. It is observed that the mechanical parameters of the material should be analyzed directly by the data of rotational angle and torque measured by the rheometer but not the apparent shear stress and strain data provided by the rheometer directly. A hyperelastic constitutive model, a 2-term reduced polynomial strain energy potential, was adopted to describe the nonlinear stress-strain relationship. The material parameters were identified and the dependency of the parameters on the temperature was analyzed. It's found that the modulus at small deformation decreases with increasing temperature following an approximately linear relationship; while, the modulus at large deformation showed a process of first increasing and then decreasing with increasing temperature.